Prevalence of TMPRSS2-ERG and SLC45A3-ERG gene fusions in a large prostatectomy cohort - Esgueva, Raquel (2010)
The majority of prostate cancers harbor recurrent gene fusions between the hormone-regulated TMPRSS2 and members of the ETS family of transcription factors, most commonly ERG. Prostate cancer with ERG rearrangements represent a distinct subclass of tumor based on studies reporting associations with histomorphologic features, characteristic somatic copy number alterations, and gene expression signatures. The current study describes the frequency of ERG rearrangement prostate cancer and three 5 prime (5') gene fusion partners (i.e., TMPRSS2, SLC45A3 and NDRG1) in a large prostatectomy cohort. ERG gene rearrangements and mechanism of rearrangement, as well as rearrangements of TMPRSS2, SLC45A3, and NDRG1 were assessed using fluorescence in-situ hybridization (FISH) on prostate cancer samples from 614 patients treated by radical prostatectomy. ERG rearrangement occurred in 53% of the 540 assessable cases. TMPRSS2 and SLC45A3 were the only 5' partner in 78% and 6% of these ERG rearranged cases, respectively. Interestingly, 11% of the ERG rearranged cases demonstrated concurrent TMPRSS2 and SLC45A3 rearrangements. TMPRSS2 or SLC45A3 rearrangements could not be identified for 5% of the ERG rearranged cases. From these remaining cases we identified one case with NDRG1 rearrangement. We did not observe any associations with pathologic parameters or clinical outcome. This is the first study to describe the frequency of SLC45A3-ERG fusions in a large clinical cohort. Most studies have assumed that all ERG rearrangement prostate cancers harbor TMPRSS2-ERG fusions. This is also the first study to report concurrent TMPRSS2 and SLC45A3 rearrangements in the same tumor focus suggesting additional complexity that had not been previously appreciated. This study has important clinical implications for the development of diagnostic assays to detect ETS rearrangement prostate cancer. Incorporation of these less common ERG rearrangement prostate cancer fusion assays could further increase the sensitivity of these PCR-based approaches.